Structural and Magnetic Properties of Multiferroic TbMn0 3 and quasi-one Dimensional Quantum Spin System LiCuV04 - Kumar, Abhishek (iit bhu varanasi, 2015)
In everyday life of human being. they need many devices e.g. mobile. computer. pen drive, transistor etc. All the devices cannot be carried every time at any place. So, miniaturization of devices with multifunction come into the life e.g. smartphone which are used for multipurpose. It is possible only by developing multifunctional materials.
This thesis submitted by IITBHU Varanasi Phd scholar and supervised by Prof. Sandip Chaterjee
Keywords: Quantum spin System; Magnetic Properties of Multiferroic